Online Learning Program Evaluation in The Covid-19 Pandemic Era Using The CIPP Model - Sophia Tri Satyawati; Menik Purpuniyanti; Sri Katoningsih (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The objective of this study is to evaluate the online learning program from using CIPP model which was focused on explaining the online learning system program in terms of the Context, Input, Process, Product components. The method used in this research was mixed method research with a descriptive approach. The quantitative data was collected using a questionnaire for 140 students, while the qualitative data used interview techniques with the principal, coordinator of the curriculum field, and two teacher representatives at SMA Negeri 1 Wonosegoro 1. The results of the study concluded that the level of achievement of the online learning system program in the Context component averaged 70.20% in ‘Good’ category; the Input component averaged 67.96% in ‘Good’ category; the Process components averaged 39.65% in ‘Poor’ category; and the Product components averaged 36.53% in ‘Poor’ category. The average score for all components was 53.59% categorized as sufficient. From the research results, it can be concluded that the online learning system program from home at SMA Negeri 1 Wonosegoro as a whole is sufficient, so there is still a need for improvements.